Bispecific VH/Fab antibodies targeting neutralizing and non-neutralizing Spike epitopes demonstrate enhanced potency against SARS-CoV-2 - Shion A. Lim; Josef A. Gramespacher; Katarina Pance; Nicholas J. Rettko; Paige Solomon; Jing Jin; Irene Lui; Susanna K. Elledge; Jia Liu; Colton J. Bracken; Graham Simmons; Xin X. Zhou; et al. (mAbs, 2021)
Numerous neutralizing antibodies that target SARS-CoV-2 have been reported, and most directly block binding of the viral Spike receptor-binding domain (RBD) to angiotensin-converting enzyme II (ACE2). Here, we deliberately exploit non-neutralizing RBD antibodies, showing they can dramatically assist in neutralization when linked to neutralizing binders. We identified antigen-binding fragments (Fabs) by phage display that bind RBD, but do not block ACE2 or neutralize virus as IgGs. When these non-neutralizing Fabs were assembled into bispecific VH/Fab IgGs with a neutralizing VH domain, we observed a ~ 25-fold potency improvement in neutralizing SARS-CoV-2 compared to the mono-specific bi-valent VH-Fc alone or the cocktail of the VH-Fc and IgG. This effect was epitope-dependent, reflecting the unique geometry of the bispecific antibody toward Spike. Our results show that a bispecific antibody that combines both neutralizing and non-neutralizing epitopes on Spike-RBD is a promising and rapid engineering strategy to improve the potency of SARS-CoV-2 antibodies.